Analysis of tourists’ opinions about the receptive tourist services in the municipality of Ouro Preto on platforms Instagram, Tripadvisor e Google Meu Negócio - Teixeira, Thalita Stephanie; Carvalho, Ivan Aguiar; Silva, Yara Pereira da; Teixeira, Stéphani dos Santos; Braga, Solano de Souza; Freitas, Lara Brunelle Almeida (Anais Brasileiros de Estudos Turísticos, 2024)
The chain of tourist services involves many areas, and can be the great competitive advantage of a municipality. It includes the tourist reception sector, which involves a diverse range of actions and services, the focus of this article. The general objective was to analyze the evaluations of the Ouro Preto tourist destinations on the TripAdvisor and Google Meu Negócios platforms, and the profile of these enterprises on Instagram, in order to understand how their digital presence has been consolidating. From this, this article analyzes the perceptions of tourists in relation to establishments in the municipality of Ouro Preto, Minas Gerais. Netnography was used as a methodological strategy with mixed treatment of information collected on Instagram, TripAdvisor and Google Meu Negócios platforms. It was possible to conclude the low use of platforms by receptive tourism agencies in Ouro Preto, as well as the need for training local businessmen to use such resources.